Optimized NMR Experiments for the Isolation of I=1/2 Manifold Transitions in Methyl Groups of Proteins. Issue 1 (5th December 2019) - Tugarinov, Vitali; Karamanos, Theodoros K.; Ceccon, Alberto; Clore, G. Marius
Abstract: Optimized NMR experiments are developed for isolating magnetization belonging to the I =1/2 manifolds of 13 CH3 methyl groups in proteins, enabling the manipulation of the magnetization of a 13 CH3 moiety as if it were an AX ( 1 H‐ 13 C) spin‐system. These experiments result in the same 'simplification' of a 13 CH3 spin‐system that would be obtained from the production of 13 CHD2 ‐methyl‐labeled protein samples. The sensitivity of I =1/2 manifold‐selection experiments is a factor of approximately 2 less than that of the corresponding experiments acquired on 13 CHD2 ‐labeled methyl groups. The methodology described here is primarily intended for small‐to‐medium sized proteins, where the losses in sensitivity associated with the isolation of I =1/2 manifold transitions can be tolerated. Several NMR applications that benefit from simplification of the 13 CH3 (AX3 ) spin‐systems are described, with an emphasis on the measurements of methyl 1 H‐ 13 C residual dipolar couplings in a 13 CH3 ‐methyl‐labeled deletion mutant of the human chaperone DNAJB6b, where modulation of NMR signal intensities due to evolution of methyl 1 H‐ 13 C scalar and dipolar couplings follows a simple cosine function characteristic of an AX ( 1 H‐ 13 C) spin‐system, significantly simplifying data analysis. Abstract : Optimized NMR pulse schemes are developed for a more efficient and complete isolation of magnetization belonging to I =1/2 manifolds in methyl groups of proteins.